Markers of Increased Aeration in the Paranasal Sinuses and Along the Skull Base: Association between Anatomic Variants. Issue 6 (November 2014) - Rereddy, Shruthi K.; Johnson, David M.; Wise, Sarah K.
Background: There may be substantial variation in paranasal sinus pneumatization across patients and between right and left sides. Patients with extensive sinus aeration, especially of the sphenoid sinus and along the skull base, often have protrusion of critical structures into the pneumatized sinus cavities, which potentially places these structures at risk during sinus surgery. Objective: To evaluate associations between anatomic markers of increased paranasal sinus aeration along the skull base and to determine whether the presence of certain markers predicts other critical anatomic variants. Methods: Submillimeter axial computed tomography (CT) scans and associated triplanar reconstructions from 100 subjects were reviewed for the presence of 22 anatomic variants by two separate evaluators. Twelve of these variants were selected as markers of increased pneumatization. Average numbers of markers were compared with t-tests; associations between markers were evaluated by logistic regression analyses. The Holm-Bonferroni method was used to correct for multiple tests. Results: Five anatomic variants were associated with increased paranasal sinus pneumatization as define by total number of markers of pneumatization: anterior ethmoid artery below the skull base, dehiscent/protruding internal carotid artery (ICA), dehiscent/protruding optic nerve (ON), pneumatized pterygoid recess, and middle turbinate (MT) concha bullosa (all p < .02). Significant associations were found between pneumatized pterygoid recesses and dehiscent or protruding ONs (odds ratio [OR] 3.06, p = .0120), dehiscent or protruding ICAs (OR 6.64, p < .0001), and anterior ethmoid arteries below the skull base (OR 2.65, p = .0189). Significant association was also found between dehiscent or protruding ONs and dehiscent or protruding ICAs (OR 3.57, p = .0047). Conclusion: The markers of increased pneumatization and anatomic associations identified is study have important implications for surgeons planning and undertaking operative approaches in and around the sinuses.